Assembly of light‐emitting diode based on hydrophilic CdTe quantum dots incorporating dehydrated silica gel. (21st July 2015) - Du, Jinhua; Wang, Chunlei; Xu, Xiaojing; Wang, Zhuyuan; Xu, Shuhong; Cui, Yiping
Abstract: Stable photoluminescence QD light‐emitting diodes (QD‐LEDs) were made based on hydrophilic CdTe quantum dots (QDs). A quantum dot‐inorganic nanocomposite (hydrophilic CdTe QDs incorporating dehydrated silica gel) was prepared by two methods (rotary evaporation and freeze drying). Taking advantage of its viscosity, plasticity and transparency, dehydrated silica gel could be coated on the surface of ultraviolet (UV) light LEDs to make photoluminescence QD‐LEDs. This new photoluminescence QD‐LED, which is stable, environmentally non‐toxic, easy to operate and low cost, could expand the applications of hydrophilic CdTe QDs in photoluminescence. Copyright © 2015 John Wiley & Sons, Ltd.